Isbat Nikah Over Siri Marriage In Indonesia - Sarana Abdul Hamid; Adang Djumhur Salikin (Ann Publisher, 2025)
Background. Serial marriage is a socio-religious phenomenon that continues to take place in Indonesian society. Although it is legally recognized, this marriage has no legal force because it is not recorded with the state administration. This raises legal problems, especially regarding the protection of the rights of wives, children, and family members, as well as family legal status. Isbat nikah, as a legal instrument available in the Compilation of Islamic Law and Supreme Court Regulations, is a formal solution to provide legal certainty for serial marriage. However, the practice of its application in court still faces various obstacles, both from a juridical and a sociological perspective, as well as from a substantive justice perspective. Purpose. This study aims to reconstruct the position of isbat nikah over serial marriage with a normative-juridical and sociological approach. Method. This article uses normative legal research methods with the following approaches: Legislation, examining Law No. 1/1974, KHI, Law No. 7/1989 jo. Law No. 50/2009 on Religious Courts, with the study topic: Conceptual, discussing the views of fuqaha on marriage and registration. A legal comparison, reviewing the practice of legalizing marriage in several Muslim countries. Maqāṣid al-syarī'ah assesses the suitability of isbat nikah with the principles of protection of religion, soul, descent, property, and honor. Conclusion. The results of the study show the need for legal reform through the reinterpretation of norms, harmonization of regulations, and the strengthening of the principles of justice and family protection, so that isbat nikah is not only a formal legalization but also an instrument for protecting family rights.